PENGARUH KUALITAS PELAYANAN FISKUS, DENDA PAJAK, DAN PENERAPAN SISTEM SAKPOLE TERHADAP KEPATUHAN WAJIB PAJAK DI KANTOR SAMSAT KOTA SURAKARTA - Sugiyani, Fitria; Ningsih, Suhesti; Dewi, Maya Widyana; Ningrum, Mutiara Asri (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the Quality of Fiscal Services, Tax Fines, and the Implementation of the Sakpole System on Taxpayer Compliance. The population in this study were motorized vehicle taxpayers registered at the Surakarta City Samsat Office with an accidental sampling method of 100 people. Based on the Slovin formula, with an error rate of 10%. The analysis technique in this study consisted of descriptive statistical analysis, instrument testing, classical assumption test, and hypothesis testing. The results of this study prove the results of the regression in the regression equation that the Quality of Fiscus Service, Tax Fines and the Implementation of the Sakpole System have a positive effect on Taxpayer Compliance. The results of the F test and t test show that the Quality of Fiscal Services, Tax Fines, and the Implementation of the Sakpole System have a positive and significant effect on Taxpayer Compliance. And based on the results of the R2 test (coefficient of determination) it is known that the Quality of Fiscal Services, Tax Fines, and the Application of the Sakpole System are able to explain 49.8% of the taxpayer compliance variable registered at the Surakarta City Samsat Office, while 50.2% is influenced by the variable other things that were not investigated, such as tax socialization, tax system, tax reform and others.